Political Economy and Political Power: The American State and Finance in the Neoliberal Era. Issue 3 (22nd May 2014) - Panitch, Leo; Gindin, Sam
<x content-type="archive" xml:space="preserve">Abstract</x> Understanding the role of the American state in the era of neoliberal finance requires a scale of analysis that can identify not only the domestic but also the international role of the informal empire the US established in the middle of the twentieth century for superintending capitalism on a world scale. This article demonstrates that it was not so much neoliberal ideology that broke the old system of financial regulations, as it was the latter's increasingly dysfunctional effects as finance outgrew the New Deal incubator through the post-war decades. Through the Bretton Woods crisis and the stagflation of the 1970s, institutional reform in the financial sector became a key dimension of broader competitive capitalist strategies for innovation and expansion. While this certainly involved extensive leveraging and speculation, it met the hedging needs not only of financial institutions but also of the many corporations seeking protection from the rapidly evolving vulnerabilities associated with global trade and investment. Yet the financial volatility that inevitably resulted from those very transformations meant that the Federal Reserve's function as lender of last resort was increasingly called upon, just as the Treasury came to define its role as that of 'failure containment' on a global scale. On the basis of this theoretical and historical perspective, the article analyses the causes and consequences of the 2007–8 financial crisis and the 'old/new practice of failure containment' that has characterized the American state's response to it.